Crow talk : a novel - Garvin, Eileen (Dutton, 2024)
"Nationally bestselling author of The Music of Bees Eileen Garvin returns with a moving story of hope, healing, and unexpected friendship set amidst the wild natural beauty of the Pacific Northwest"--